Perancangan Aplikasi Rental Mobil Dengan Framework CodeIgniter - Putry Wahyu Setyaningsih; Irfan Juliardi Saputra (Fakultas Teknik Universitas Hamzanwadi, 2021)
Car rental is a type of business that is engaged in four-wheeled vehicle rental transportation. With the current technological developments greatly affect the quality in the field of car rental services. Several fields that use information technology are education, agriculture and companies have used information technology to facilitate quick, precise and accurate information to the public. The development of technology is not only used for a field or large-scale company, but can be used by various groups of people to support a business they manage. One of the businesses that utilize this information technology is Sakti car rental, which is engaged in transportation for four-wheeled vehicle rental services. Currently, four-wheeled transportation has become a necessity to support the daily mobility of all people. Data management on Sakti Car Rental still uses manual methods which often cause errors. Technological developments also allow the development of a programming language, one of which is the CodeIgniter Framework. Therefore, the author designed a car rental application with a codeigniter framework that aims to make it easier for owners to manage car data, transaction data and to print transaction reports and avoid errors.